Produção de histórias em quadrinhos (HQ) no processo de aprendizagem da leitura e da escrita - Almeida, Maria de Lourdes Oliveira (2019)
In this study, we approach the reading and writing of Comic Books (HQ). We aim to awaken the taste for reading to form young creative, autonomous and critical, proficient readers and writers, through reading comics, a genre that explores imagery and verbal languages. We explored the importance of reading in educational formation, especially in Portuguese language teaching, since it is mainly from this that the student will succeed in school and in social life. The student's teaching and learning process in relation to writing is a continuation of the study of reading, since it is not possible to work writing without reading as a medium. It is up to the teacher to formulate new strategies in the teaching of these two knowledge, thus, we use as methodological innovation the reading, analysis and production of HQ by the students. It was from these productions that the students increased their contact in the classroom, mainly in relation to reading and writing. In the elaboration of the HQ we resort to socio-environmental issues, focusing on the conscious use of water in school; After the production of the HQ, we elaborated and applied the game "Orchestral Bingo", because we noticed precarious dominance in relation to the orthographic choices. In addition to developing phonological awareness, "Bingo" activates already accumulated knowledge and causes healthy competition for the playful character of the game. Work was done with the group of the 6th year of Elementary School of the State College Vitória de Santa Maria, in Aracaju / SE. The activities were applied in ten classes, of fifty minutes each, during the month of July 2018. We used as an instrument to diagnose reading and writing levels of the students two activities titled as entrance test and exit test, both analyzed, the from the criteria established in the barema, with the purpose of evaluating students' evolution in a qualitative and quantitative manner, divided into parameters and levels. In the entrance test, we observed that the writing of the students presents learning lag with respect to the domain of the orthographic rules, revealing absence of mastery of elementary rules such as: typing with lowercase beginnings of sentences, absence of punctuation, accentuation, syllabic separation, and also the writing of the sibilant -S. A percentage of 34.3% of the students presented difficulties in relating the sound to the letter to be written; in relation to the total number of students. A small percentage of 6.2% was able to attend to the command for the production of the text, but a very significant quantitative has already internalized the elements of a narration, its characteristics, the process of dialogue and its adequations. In the test of exit we recorded an improvement in the results: the productions were adapted to the writing, observing the prescriptions of the orthographic and grammatical rules; there was a very significant result in the textual construction, regarding the typology, in the case the proposal of a comic book sequence, in a progressive way in search of a unity of meaning; we also see a gradual increase in the textual and pragmatic elements. We conclude in this way that the relevant role of reading and writing as a social practice in Portuguese Language classes, with the purpose of helping students to understand the purpose of developing the writing ability in the standards agreed by the standard language, is necessary to the formation of the citizen in order to enable him to meet the demands demanded by the literate society of the 21st century.